A Needs Analysis of Problem-Based Learning Media Using the Design Thinking Framework to Improve Critical Thinking - Sri Rahayu; Aryo Andri Nugroho; Nizaruddin (Postgraduate, University of Mataram, 2025)
Low mathematics achievement in Indonesian secondary schools persists despite ongoing curriculum reforms. This study employed a Design Thinking–guided mixed-method inquiry to analyse instructional needs and co-create a multimedia Problem-Based Learning (PBL) model that fosters critical thinking. Three purposively selected schools in Batam contributed three mathematics teachers and forty-two students. Data were gathered through two rounds of semi-structured interviews, classroom observations, and Google-Form questionnaires. Qualitative coding during the Empathise and Define stages revealed four central issues: limited transfer of concepts to problem contexts, weak foundational mastery, mismatch between learning media and student preferences, and scarce collaborative support. Only 7.2 % of students felt competent, whereas 83.3 % acknowledged frequent computational errors and 80 % were unable to apply formulas. Students preferred group discussion (67.7 %), peer tutoring (51.6 %), and audio-visual media (45.2 %). In the Ideate stage, a PBL sequence aligned with the TPACK framework was prototyped and pilot-taught in each school. Observation indicated that 67.7 % of learners participated actively in group problem-solving, while post-lesson feedback showed 74.4 % experienced clearer conceptual understanding when multimedia and peer support were combined. Teachers reported improved lesson flow and greater responsiveness to heterogeneous ability levels. The study concludes that Design Thinking, coupled with media-rich PBL, can realign pedagogy with stakeholder needs, strengthen critical-thinking dispositions, and serve as a replicable model for mathematics instruction in similar contexts. Future work should examine long-term learning gains, scalability across diverse regions, and professional development structures required to sustain technology-enhanced PBL adoption. Such evidence will clarify policy guidelines and funding priorities for equitable implementation nationwide.